Finite element stress analysis after simulated canal preparation using two different methods: An In vitro study - P C Sasidhar; Kiranmayi Govula; Lavanya Anumula; Kowmudi Maddineni (Wolters Kluwer Medknow Publications, 2023)
Background: The success of root canal treatment and the amount of surviving dentin tissue around the root canals determine the prognosis of root canal-treated teeth. Stainless steel or nickel-titanium (NiTi) file can prepare the root canal biomechanically. The widespread use of NiTi equipment has improved the predictability of the crucial phase of root canal treatment. Aim and Objective: This study aimed to evaluate and compare the stresses generated by rotary and reciprocatory files in straight and curved canals. Methodology: Computer-assisted design models of mandibular premolars with straight and curved root canals and rotary and reciprocatory files were made per the detailed drawings. After preprocessing, node-to-node connections were made, boundary connections were defined and subjected to stress application, which was analyzed using finite element analysis. Results: The maximum von Mises stress under a vertical load of 12.5 N that appeared in the curved canal with rotary motion was 40.287 Mpa. Reciprocatory action produces fewer stresses than rotary motion. The maximum von Mises stresses under a vertical load of 12.5 N appeared in straight root with reciprocatory movement (18.697 Mpa). The peak of von Mises stresses under a vertical load of 12.5 N appeared in curved roots with reciprocatory motion was 27.524 Mpa. The results might be attributed to the salient design of the rotary instrument and its continuous motion during the simulated canal preparation, which reduces the compacting forces of the obturating material. Conclusion: Within the study's limitations, it can be stated that the rotary group had higher stress distribution in both straight and curved canals than the reciprocatory group in dynamic analysis. On static analysis, the rotary group has shown a lower amount of stress when compared to the reciprocating group in both straight and curved canals. There was no significant difference between the two analyses.